Criticism Against Violence For Solving Problem Reflected In William Somerset Maugham's Liza Of Lambeth Novel (1897):A Sociological Perspective - Anggraeni, Dyahretno; , Dr.M.Thoyibi,M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This study is about Criticism Against Violence for Solving Problem in Liza of Lambeth novel. The problem of the study is criticism against violence for solving problem reflected in Liza of Lambeth novel. The object of the study is Liza of Lambeth novel by William Somerset Maugham. It uses sociological perspective. This study belongs to qualitative research. In this method, there are two types of data source, namely primary and secondary data source. The primary data source is the novel an the secondary data is other materials related to the study. The result of the study shows that based on the analysis there is a close relation between the novel and the social reality in English in the end nineteenth century. William Somerset Maugham wants to criticize the violence for solving problem in Liza of Lambeth novel.